2019
DOI: 10.1039/c9cp02129a
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial capacitance immunosensing using interdigitated electrodes: the effect of insulation/immobilization chemistry

Abstract: With the aim of improving the reproducibility of capacitive immunosensors, we performed a comparative study of four different insulating/immobilization chemistries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 42 publications
3
37
0
Order By: Relevance
“…For example, decreasing the spacing between interdigitated electrodes will reduce the influence of . Also, electrodes with a thin conformal coating of insulative material would enhance the stability and sensitivity of the capacitance measurement ( Castiello et al, 2019 ). Future tests will determine if measurements acquired at other frequencies and/or voltages ( i.e., other than 10 kHz, 22 mV) will further improve platform performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, decreasing the spacing between interdigitated electrodes will reduce the influence of . Also, electrodes with a thin conformal coating of insulative material would enhance the stability and sensitivity of the capacitance measurement ( Castiello et al, 2019 ). Future tests will determine if measurements acquired at other frequencies and/or voltages ( i.e., other than 10 kHz, 22 mV) will further improve platform performance.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of capacitive immunosensors can be adjusted by modifying the electrode surface area, insulation (coating) layer, and the electrode and coating material. Highly sensitive sensors can be achieved by making thin conformal coating layer which ensure stable capacitance changes in response to probe/target binding ( Castiello et al, 2019 ). Several studies reported the use of capacitance immunosensors for detection of pathogens ( Cesewski and Johnson, 2020 , Hanna et al, 2006 , Luka et al, 2019 , Teeparuksapun et al, 2012 , Wang et al, 2019 , Wang et al, 2017 ), thus demonstrating that it can be used as a reliable label-free sensing method.…”
Section: Introductionmentioning
confidence: 99%
“…For example, decreasing the spacing between interdigitated electrodes will reduce the influence of Rsus. Also, electrodes with a thin conformal coating of insulative material would enhance the stability and sensitivity of the capacitance measurement (Castiello et al (2019)). Future tests will determine if measurements acquired at other frequencies and/or voltages ( i.e ., other than 10 kHz, 22 mV) will further improve platform performance.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of capacitive im-munosensors can be adjusted by modifying the electrode surface area, insulation (coating) layer, and the electrode and coating material. Highly sensitive sensors can be achieved by making thin conformal coating layer which ensure stable capacitance changes in response to probe/target binding (Castiello et al (2019)). Several studies reported the use of capacitance immunosensors for detection of pathogens (Cesewski and Johnson (2020); Hanna et al (2006); Luka et al (2019); Teeparuksapun et al (2012); Wang et al (2019, 2017)), thus demonstrating that it can be used as a reliable label-free sensing method.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, an increase in charge transfer resistance (Rct) occurs. Regarding capacitive biosensors, antibodies [30][31][32][33], aptamers [34,35], and affimers [36] have been used as recognition elements. Capacitive biosensors rely on changes occurring within the electrical double layer (EDL), where the thickness is changed according to binding of a target to a recognition element on the electrode.…”
Section: Measurement Of Fructosyl Lysine and Ga With An Ide Enzyme Sementioning
confidence: 99%